Nanomaterial for inorganic pollutant remediation - Jusoh, Muhammad Noor Hazwan; Yap, Chi Nam; Hadibarata, Tony; Jusoh, Hisyam; Najib, Mohamed Zuhaili Mohamed (Environmental and Toxicology Management, 2021)
Heavy metal (loids) in wastewater persists as a contagious and non-biodegradable environmental pollutant. With the ever rising of nanotechnologies in various field, there is a mass flux of heavy metal (loid)s being transmitted in many water sediments includes wastewater and rivers in which difficult to eliminate through conventional treatment processes. The introduction and development of nanomaterials have been increasingly utilized. Their high absorption capacity and unique properties in eliminating heavy metal pollutants and other nano pollutants have been extensively used in the remediation of inorganic pollutants. This review study illustrates the different types of nanomaterials that are utilized in various treatment process such as nano zero-valent iron (nZVI), carbon nanotubes and titanium dioxide nanoparticles (TiO2NPs). The mechanism of each nanomaterial and also its advantages and disadvantages are being portrayed. The identified factors affecting their efficiency in eliminating heavy metal and other inorganic pollutants are briefly described.